Hybrid effect of carbon nanotubes and polypropylene microfibers on fire resistance, thermal characteristics and microstructure of cementitious composites - Mohammad R. Irshidat (8047913) (2021)
The current study experimentally investigates the hybrid effect of carbon nanotubes (CNTs) and polypropylene (PP) microfibers on fire resistance and thermal characteristics of cementitious composites. Cement mortar with small dosages of CNTs and PP fibers are prepared and heated at 150 °C, 200 °C, 450 °C, and 600 °C. The residual mechanical properties, microstructure deterioration, and thermal properties of heated mortar are reported. The results shows the ability of the CNTs to enhance the residual compressive and flexural strengths of PP fiber-reinforced mortar exposed to elevated temperature up to 600 °C. Residual fracture energy is improved by adding small dosage of PP microfibers and CNTs. The improvement was less significant in the case of exposure temperatures greater than melting point of the fibers. Thermal conductivity of cement mortar is increased by the addition of the CNTs but not the PP fibers for all heating levels. According to the DSC and TGA analysis, presence of CNTs increased heat absorption needed for decomposition of the hydration products of cement mortar whereas the presence of the fibers has minor effect. SEM images show that the CNTs filled the pores and delayed the initiation of the cracks, whereas the PP fibers bridged these cracks and mitigated their propagation. Other Information Published in: Construction and Building Materials License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.conbuildmat.2020.121154